Safe use of hospital information systems: an evaluation model based on a sociotechnical perspective - Salahuddin L.; Ismail Z.; Raja Ikram R.R.; Hashim U.R.; Idris A.; Ismail N.H.; Hassan N.H.; Abdul Rahim F. (Taylor and Francis Ltd., 2023)
Errors; Hospitals; Instrument testing; Medical computing; Medical information systems; Quality control; Reliability analysis; Software design; Surveys; Conceptual model; Hospital information systems; Malaysian governments; Predictive capabilities; Safe use; Socio-technical perspective; Sociotechnical; Structural equation modelling (SEM); Information use; article; construct validity; error; factor analysis; government; hospital information system; human; human experiment; mediator; physician; questionnaire; reliability; software design; structural equation modeling; teamwork